Synergistic Enhancement of Vanadium Redox Flow Batteries via Carbon Nanotube-Decorated and Thermally-Acid Activated Carbon Felt Electrodes - Rashid Nadimi, Sahar; Zarei Jaliyani, Mohammad (Mechanical Technology and Engineering Insights, 2024)
In recent years, Vanadium Redox Flow Batteries (VRFBs) have attracted significant attention as an important energy storage technology. These batteries are considered among the advanced energy storage systems that offer unique capabilities for power generation applications and other industrial uses. Today, the integration of this technology with solar power plants, wind farms, and thermal power stations has experienced substantial growth. Each vanadium redox flow battery cell consists of two half-cells separated by a proton exchange membrane. In addition, every single cell contains two electrodes that serve as the active sites for electrochemical reactions, through which chemical energy is converted into electrical energy. Carbon felt is one of the commonly used electrode materials in vanadium batteries. The objective of this study is to introduce an effective method for activating the surface of Carbon felt electrodes using Carbon Nanotubes (CNT), in such a way that electrochemical processes proceed at higher reaction rates, thereby enhancing the overall efficiency and performance of VRFBs.